Understanding the adoption of crop protection smartphone apps: An application of the Unified Theory of Acceptance and Use of Technology - Marius Michels; Vanessa Bonke; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2019)
There is a steady increase in smartphone apps available to improve farmers' decision making with respect to crop protection. While current studies have focused on smartphone adoption in general and farmers' general willingness to pay for crop protection smartphone apps, none have focused on the initial adoption decision. Furthermore, it has not been studied yet which app functions are perceived as useful and which are actually used by farmers. Based on an online survey of 207 German farmers conducted in 2019, we investigated farmers' adoption decision for crop protection smartphone apps based on the Unified Theory of Acceptance and Use of Technology (UTAUT) framework applying partial least squares equation modelling and a binary logit model. Descriptive results show that 95 % of the surveyed farmers use a smartphone, but only 71 % use a crop protection smartphone app. Apps providing infor-mation about weather, pest scouting and infestations forecasts are perceived as most useful by the majority of farmers. However, reported use fell short of reported usefulness. All hypothe-ses of the UTAUT model could be verified. 72 % of the variation in the behavioral intention to use a crop protection smartphone app and 50 % of the variation in the actual adoption is explained by the model. The results are of interest for policy makers in the field of digitaliza-tion in agriculture as well as providers and developers of crop protection smartphone apps.
Keywords: 330; crop protection; partial least squares structural equation modelling; precision agriculture; smartphone; smartphone apps; unified theory of acceptance and use of technology